Development of a database on genetic characterization of animal genetic resources - Avnish Kumar Bhatia; Meenakshi Arora; Aditi Sharma; Pardeep Gupta; Reena Arora; Birham Prakash (Journal of Livestock Biodiversity, 2025)
Conservation of breeds of domestic animal species is essential to preserve genetic diversity and maintaining future breeding options. Phenotypic and genetic characterisation of breeds has been taken up all over the globe as a prerequisite for conservation. Detailed genetic data on within and between-breed diversity are essential for effective management of Farm Animal Genetic Resources. Only few databases are available on this aspect. This paper reports development of a database on genetic characterisation using microsatellite markers. The database contains genetic diversity parameters of breeds as reported in published studies. It has uses as a source of composite information at one site and for comparing genetic diversity of breeds for making decision on their prioritisation for conservation.